CLUES FROM MIS 11 TO PREDICT THE FUTURE CLIMATE - A MODELLING POINT OF VIEW - Loutre M.F. (My University, 2003)
Simulations performed with the LLN two-dimensional Northern Hemisphere climate model have confirmed that climate is largely triggered by changes in insolation forcing although atmospheric CO2 concentration also plays an important role, in particular in the amplitude of the simulated variations. Marine isotope stage 11 (MIS 11) some 400 kyr ago and the future share a common feature related to climate forcing, i.e. the insolation at these times displays small similar variations. MIS 11 can be considered an analogue for future natural climate changes. Different simulations were performed to identify the conditions constraining the length of the MIS 11 simulated interglacial. Clearly its length strongly depends on the phase relationship between insolation and CO2 variations. It is only when insolation and CO2 act together towards a cooling, i.e. they both decrease together, that the climate enters quickly into glaciation and that the interglacial may be short. Otherwise each forcing alone is not able to drive the system into glaciation and the climate remains in an interglacial state. The same situation applies for the future. However, we already know that CO2 and insolation do not play together. Indeed, insolation has been decreasing since 11 kyr BP and CO2 concentration remains above 260 ppmv, with a general increasing trend over the last 8000 yr. Therefore we conclude that the long interglacial simulated for the future is a robust feature and the Earth will not enter naturally into glaciation before 50 kyr AP.